Merkel cell carcinoma: Epidemiology, disease presentation, and current clinical practice outcomesCapsule Summary - Marita Yaghi, MD; Paul Benedetto, MD; John Greskovich, MD; Roger Haber, MD; Barbara Dominguez, MBA; Hong Liang, PhD; Zeina Nahleh, MD; Rafael Arteta-Bulos, MD (Elsevier, 2022)
Using the National Cancer Database, we introduce the findings of a retrospective investigation of the largest cohort of cases with Merkel cell carcinoma (N = 20,829). A decreasing proportion of stage I (P = .0004) and stage II (P = .0065) Merkel cell carcinoma among skin cancers was complemented by an increasing proportion of stage III disease (P < .0001). A predominance of non-Hispanic White (96.4%), male (62.6%) patients with a mean age of 74.5 ± 10.8 years and Medicare coverage (73.5%) was observed. Stage I was the most common presenting stage at diagnosis (29.2%), followed by stages II (12.7%), III (11.0%), and IV (3.8%). Most Merkel cell carcinoma tumors grew outside the head and neck (53.4%) and showed a nodular growth pattern (66.0%) but no extracapsular lymph node (90.5%) or lymphovascular involvement (63.8%). Narrow-margin excision and radiation therapy (RT) were used in 75.2% and 56.3% of tumors, respectively. Wide-margin excision lead to improved overall survival (P < .001) versus narrow-margin excision, particularly in stage III (difference in the median overall survival rate [ΔmOS], 23.7 months; P < .001). RT showed a significant OS benefit (P =.006), most pronounced in stage II (ΔmOS, 37.8 months) followed by stage I (ΔmOS, 16.1 months; P < .001). The survival benefit with primary-site RT (ΔmOS, 24.0 months) was higher than that with primary-site/lymph node RT (ΔmOS, 5.2 months; P < .001). Wide-margin excision independently predicted improved OS (hazard ratio, 0.577; 95% CI, 0.403-0.826; P = .003) versus narrow-margin excision and RT predicted better OS (hazard ratio, 0.608; 95% CI, 0.424-0.873; P = .007) versus no RT on multivariable analysis.